PENDEKATAN GREEN LEAN SIX SIGMA UNTUK MINIMISASI LIMBAH DALAM PRODUKSI PRODUK GELAS DI INDUSTRI PERALATAN PLASTIK RUMAH TANGGA - Rizkika, Adelia Dwi; Kosasih, Wilson; Salomon, Lihrone Laricha (Universitas Tarumanagara, 2025)
This research was conducted at a company that produces household plastic equipment by implementing the Green Lean Six Sigma approach. The method used in this research is DMAIC (Define, Measure, Analyze, Improve, Control). At the identification stage, waste analysis was carried out using the VALSAT tool, which revealed that the main wastes occurred in the aspects of waiting and product defects. In addition, this research also measured the liquid and solid waste generated due to defective products. The usage of water and materials in the production process was measured and used as indicators to evaluate environmental aspects. The analysis results showed that the company's initial efficiency was 27.91%, with a Defects Per Million Opportunities (DPMO) rate of 5320.19 and a sigma level of 1.358. These findings indicate the need for more attention to process improvement. Improvement recommendations were made based on identifying the root causes of problems using a fishbone diagram and Risk Priority Number (RPN) analysis from Failure Mode and Effects Analysis (FMEA), resulting in prioritized recommendations to address defective products and generated waste. After implementing the proposed improvements, the company's efficiency increased to 73.17%. Additionally, waste management was also suggested to further enhance the company's sustainability and operational efficiency.